2006
DOI: 10.1080/10284150600576705
|View full text |Cite
|
Sign up to set email alerts
|

Green tea pain modulating effect in sciatic nerve chronic constriction injury rat model

Abstract: We investigated the effect of green tea (GT) in unilateral chronic constriction injury (CCI) to the rat scaitic nerve. Five groups (n = 6 rats/group) sham group: rats which underwent operation but with no ligation to the scaitic nerve, and received tap water for two weeks before and for five weeks after the surgery. Four experimental groups underwent CCI to the right sciatic nerve, divided randomly as follows: group E were given tap water throughout the study. Group B received GT before and after CCI. Group C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Previously, we have shown that rats, suffering from chronic constrictive injury of the sciatic nerve, improved their functional behavior significantly following consumption of green tea (Renno et al 2006). In this study, both the protective and morphological recovery effects of EGCG on skeletal muscles, measured by functional behavioral recovery, desmin immunohistochemistry (IHC), and apoptotic cellular death signaling pathway, are evaluated in the context of experimental rat sciatic nerve crush injury.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we have shown that rats, suffering from chronic constrictive injury of the sciatic nerve, improved their functional behavior significantly following consumption of green tea (Renno et al 2006). In this study, both the protective and morphological recovery effects of EGCG on skeletal muscles, measured by functional behavioral recovery, desmin immunohistochemistry (IHC), and apoptotic cellular death signaling pathway, are evaluated in the context of experimental rat sciatic nerve crush injury.…”
Section: Introductionmentioning
confidence: 98%
“…Several tests of reflexive sciatic nerve function (foot position, toe spread, extensor postural thrust [EPT], and hopping tests) were conducted as described in our previous studies. 6,24 Briefly, the time course of functional recovery was measured using EPT after crush injury and EGCG treatment. EPT was measured by calculating the functional deficit in this feature; thus, a higher value indicates a poor outcome.…”
Section: Assessment Of Functional Recoverymentioning
confidence: 99%
“…Nociceptive mechanical thresholds expressed in grams were measured with an analgesic meter (model 21025; UGO Basile, Monvalle Varese, Italy), which has been previously used to measure hyperalgesia. [24][25][26] Briefly, nociceptive mechanical threshold was assessed in the different animal groups by applying a steady pressure on the hindlimb and measuring the time needed for the rat to withdraw the limb. The mean of three consecutive values were measured, and the mean -SEM of the latency periods were calculated and plotted.…”
Section: Assessment Of Functional Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Factors with anti-inflammatory properties can increase the blood flow in damaged tissues, and subsequently improve the process of wound healing and recovery [27]. Experimental evidence suggests that EGCG could inhibit TNF-alpha gene expression [28,29]. In a study performed on an animal model of multiple sclerosis, the combination of glatiramer acetate (GA) and EGCG had favorable effects on neuronal survival and axonal growth by reduced reactive oxygen species generation and reduction in the nuclear factor kappa-light-chain-enhancer of activated B cells (NFkB) [28].…”
Section: Discussionmentioning
confidence: 99%